Growth responses of corn cultivars on weed and nitrogen application. (March 2019) - Rahayu, M; Yudono, P; Indradewa, D; Hanudin, E
Abstract: This research aimed to identify the effect of weed and nitrogen dose on growth of some corn cultivars. The field research was carried out in Banguntapan, Bantul, Yogyakarta, and arranged using Randomised Completely Block Design with three replications. The treatment factors consisted of cultivars (Bisi 18, NK 33, DK 95 and Sukmaraga), weed (weed-free and weedy) and nitrogen dose (25, 150 dan 275 kg N ha −1 ). Data were analyzed using analysis of variance, continued with Duncan's Multiple Range Test at significant level of 5%. The results showed that there was no interaction between cultivar, weed, and nitrogen dose on plant height, number of leaves, stem diameter, leaf length, leaf width, and angle of the leaves. The least number of leaves on 10 weeks after planting was Sukmaraga. Weed suppressed the plant height, number of leaves, stem diameter, leaf length, leaf width and angle of the leaves, thus the plant which growth on weed-free was higher than on weedy. Nitrogen dose of 25 kg N ha −1 produced the shortest plant, the least number of leaves and the smallest stem diameter compared to the nitrogen dose of 150 kg N ha −1 and 275 kg N ha −1 .